Aportación al estudio del poblamiento y los regadíos de época romana en la cabecera del Valle del Segura. Fuentes documentales y arqueológicas - Yelo Templado, Antonio; Martínez Ortiz, Pascual; Salmerón Juan, Joaquín; Ruiz Ruiz, José (Antigüedad y Cristianismo, 1998)
About 1154 the Arab chorographer az-Zuhri followed the high course of the Segura, describing admiringly the gorge into which the river ran anci the mouth from which emerged a fountain which he called "Fuente Oscura" (Black Fountain). As he himself said, it was from this fountain that '%he Romans of Ello took water to irrigate their fertile plains". Archaeological surveys, which are being conducted from Almadenes (Cieza), are discovering the remains of Roman "villae" that run along the irrigation channels of botgh banks of the river. On the right hand side of the river near "The Gold Mountains" and dominating this landscape, are two "oppida" made with materials from the late roman period. The second of these, around which the water returns to the river is important because it marks the point where the town "La Cieza Vieja" began in the tenth century. It was said of this "oppidum" in 1579 ". .. it must have been important as can be deduced from the channel, which was taken in ancient times from the river Segura at the point that is called Almadenes and which terminated under the town".